THE EFFECT OF SELF-CONTROL, FINANCIAL LITERACY, AND RISK TOLERANCE TOWARD INVESTMENT DECISIONS AMONG STUDENTS - Ming, Yeo Wei; Keni , Keni (International Journal of Application on Economics and Business, 2025)
This study investigates the influence of self-control, financial literacy, and risk tolerance on the investment decisions of university students in Jakarta, Indonesia. The research uses a quantitative methodology to collect primary data through a Google Forms-based questionnaire. The sample comprises 120 students with prior experience in financial investments, such as stocks or mutual funds. Data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) to evaluate the relationships among the variables. The findings reveal that self-control, financial literacy, and risk tolerance all significantly and positively affect investment decisions. Specifically, self-control fosters disciplined, long-term financial planning, while financial literacy enhances students' ability to assess investment opportunities and make informed choices. Moreover, risk tolerance emerges as a critical factor, with students exhibiting higher risk tolerance being more inclined to engage in investments. The study underscores the role of psychological factors and financial education in shaping students' financial behaviors. It recommends that universities and financial institutions emphasize the development of self-control and financial literacy through targeted educational programs and customized financial products. Additionally, the study calls for future research in diverse geographical and sectoral contexts to enhance the generalizability of the findings.